Father Involvement as Moderator: Does Father’s Emotional Regulation Influence Preschooler’s Emotional Regulation? / Keterlibatan Ayah sebagai Moderator: Apakah Regulasi Emosi Ayah Memengaruhi Regulasi Emosi Anak Prasekolah? - Aninditha, Rizky; Boediman, Lia Mawarsari (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2021)
Abstract: The development of emotional regulation in early childhood can be influenced by various things, particulary the involvement of fathers. This study aimed to determine how father’s emotional regulation, as an aspect of parenting, affect the development of emotional regulation in preschoolers. The variable of father involvement was included as a moderator of the relationship between father’s emotional regulation and preschooler’s emotional regulation. Total of 118 fathers of children between the age of 3-6 years old were participatedin this study. The following measuring tools were used in this study: Difficulties in Emotion Regulation Scale (DERS), The Emotion Regulation Checklist (ERC), and The Inventory of Father Involvement (IFI) used in this study.  Linear regression statistical method was used to analyzed the data. The indicates (1) there is a significant correlation between father’s emotional regulation and preschooler’s emotional regulation (R = 0.64; R2 = 0.406; p 0.01); and (2) father involvement affects the quality of the relationship between father’s and child’s emotional regulation (Rquality= 0.72; R2 = 0.51; p 0.01; Rtime= 0.68; R2 = 0.46; p 0.01). That is, father’s involvement has a positive contribution to the relationshop between father’s emotional regulation and early childhood emotional regulation.Keywords: father involvement; father’s emotion regulation; early childhood emotion regulation; preschoolerAbstrak: Perkembangan regulasi emosi anak usia dini dapat dipengaruhi oleh berbagai hal, salah satunya faktor pengasuhan orang tua, terlebih pada keterlibatan ayah dalam pengasuhan. Penelitian ini melihat bagaimana kemampuan regulasi emosi ayah, sebagai salah satu aspek pengasuhan orang tua, memengaruhi perkembangan regulasi emosi anak usia prasekolah. Faktor keterlibatan ayah diikutsertakan sebagai moderator hubungan antara regulasi emosi ayah dengan regulasi emosi anak prasekolah. Penelitian ini melibatkan 118 orang ayah dengan anak usia 3-6 tahun. Pengukuran dilakukan dengan menggunakan alat ukur Difficulties in Emotion Regulation Scale (DERS), The Emotion Regulation Checklist (ERC), dan The Inventory of Father Involvement (IFI).  Uji statistik regresi linear digunakan untuk menganalisa data. Hasil penelitian ini menunjukkan bahwa (1) terdapat korelasi signifikan antara regulasi emosi ayah dengan regulasi emosi anak prasekolah (R = 0.64; R2 = 0.406; p 0.01); dan (2) keterlibatan ayah dalam memiliki pengaruh signifikan terhadap hubungan antara regulasi emosi ayah dengan regulasi emosi anak prasekolah (Rkualitas keterlibatan = 0.72; R2 = 0.51; p 0.01; Rjumlah waktu pengasuhan = 0.68; R2 = 0.46; p 0.01). Artinya, keterlibatan ayah dalam pengasuhan memiliki kontribusi positif terhadap hubungan antara regulasi emosi ayah dengan regulasi emosi anak usia dini.Kata Kunci: keterlibatan ayah; regulasi emosi ayah; regulasi emosi anak usia dini; anak prasekolah